Successful immunotherapy in a murine metastasizing fibrosarcoma model - Cortes, Ruben [UNESP]; Correa, Luis A. [UNESP]; Behbehani, Abdulla I. [UNESP]; Sonis, Stephen T. [UNESP]; Wilson, Richard E. [UNESP] (Wiley, 1984)
Antigenic differences were demonstrated between the primary murine fibrosarcoma and its metastases. Immunization with irradiated primary tumor cells (TC) protected C57B1/6J mice against subsequent challenge with those cells, but not against challenge with cells from pulmonary metastases (PMC). Mice immunized with irradiated PMC were protected from challenge with those cells, but not against challenge with TC. Mice with fibrosarcomas produced by the injection of 5 × 103 cells from the primary tumor were treated by resection of the tumor‐bearing limb (Amp), Amp plus cylcophosphamide (Amp+Cy), Amp plus primary TC (Amp+TC), Amp plus primary TC and from its metastatic variant (Amp + TC + PMC), and with combinations of the last two groups with Cy. Although Amp+Cy improved survival, no animal lived 100 days and metastases increased as compared to controls. Immunotherapy significantly improved survival and decreased pulmonary metastases. Antigen combinations from primary and metastatic tumors resulted in significantly better survival than did a single preparation only from TC. Chemotherapy did not enhance the results obtained with immunotherapy and surgery. Immunity conferred in long‐term survivors was permanent. Copyright © 1984 Wiley‐Liss, Inc., A Wiley Company
Keywords: antigen; fibrosarcoma; immunotherapy; murine